2020
DOI: 10.1177/2050168420911029
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion and Temporomandibular Disorders: A Long-Standing Controversy in Dentistry

Abstract: The relationship between temporomandibular disorders (TMDs) and occlusion remains controversial. Some authors believe that occlusion is the primary factor in the onset of TMD symptoms, whereas others feel that occlusion has no role in this at all. The majority of reasoning behind causation is based upon anecdotal rather than scientific evidence. Existing evidence in the literature supports the absence of a disease-specific association. This article describes this controversy and provides the reader with findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…Thilander groups observed that TMDs were significantly associated with posterior crossbite, and suggested that malocclusions should be treated orthodontically in an early age to protect against TMD [ 33 ]. In contrast, Al-Ani and Špalj et al found that symptoms of TMDs seemed to be poorly related to malocclusions [ 34 , 35 ]. Although the evidence available does not allow to establish a unambiguous relationship between malocclusions and TMD, the effects of malocclusions in growing patients of TMDs deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thilander groups observed that TMDs were significantly associated with posterior crossbite, and suggested that malocclusions should be treated orthodontically in an early age to protect against TMD [ 33 ]. In contrast, Al-Ani and Špalj et al found that symptoms of TMDs seemed to be poorly related to malocclusions [ 34 , 35 ]. Although the evidence available does not allow to establish a unambiguous relationship between malocclusions and TMD, the effects of malocclusions in growing patients of TMDs deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Other considerations indicate that remodeling capacity within the masticatory system facilitates adaptation to most occlusal functions and dysfunctions [ 6 ]. It seems to mirror the non-linear dynamics of a stress/strain curve, which is dedicated to tensegrity and living tissues [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between dental occlusion and temporomandibular disorders (TMDs) still remains controversial, inconclusive, and not fully examined [ 5 , 6 , 7 ]. Currently, etiological factors are based mainly on behavioral, psychological, and neurological components [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, there is insufficient evidence to suggest that any occlusal treatment is as effective, or more effective, than any other rehabilitation treatment in TMD. 50…”
Section: Control or Reduction Of Contributory Predisposing Factorsmentioning
confidence: 99%